Developing EFL Teachers’ Cognition of Corrective Feedback Using a Task-Based Approach - Meisam Mirzaei Shojakhanlou; Abdulbaset Saeedian (Journal of Modern Research in English Language Studies)
Investigating language teacher cognition and ways of promoting their cognition are the building blocks of teacher education because their practices are highly contingent on their cognition about underlying concepts in language pedagogy. This study explored the development of novice teachers’ cognition about corrective feedback (CF) through task-based teacher education. The data were culled from two novice Iranian English as a foreign language (EFL) teachers through a questionnaire, observation, and journal. They took part in a course centering on the ways of enhancing knowledge about CF. The course was based on task-based teacher education. The teachers were to learn and practice giving feedback through some task-based teacher education activities such as role plays and observations. The data before the course indicated that the teachers had restricted knowledge about the functions and types of CF. However, the task-based teacher education course raised the teachers’ awareness about the scaffolding potentialities of CF. They also gained insights into implicit and explicit CF types as well as their functions. In addition, CF helped them enhance their awareness about the intrusiveness of error correction in the process of communication flow. Finally, the contribution of the findings of the study for novice teachers and teacher educators and how they should educate novice teachers are discussed.